2001
DOI: 10.1086/323899
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Vancomycin‐ResistantEnterococcus faeciumInfections with Quinupristin/Dalfopristin

Abstract: Clinicians caring for patients with vancomycin-resistant Enterococcus faecium (VREF) infections face severe constraints in the selection of treatment. Quinupristin/dalfopristin (Synercid) is active in vitro against VREF, with a MIC(90) of 1.0 microg/mL. We investigated the clinical efficacy and safety of this agent in a multicenter, prospective, noncomparative, emergency-use study of 396 patients. Patients were included if they had signs and symptoms of active infection, including bacteremia of unknown origin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
54
0
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(58 citation statements)
references
References 41 publications
0
54
0
4
Order By: Relevance
“…Linezolid has inherent bacteriostatic activity (6,44) and can cause myelosuppression (45,46), and failure in bacteremia and IE has been documented in animal studies and human case reports (47)(48)(49)(50). The use of quinupristin-dalfopristin is also limited, because it demonstrates inherent bacteriostatic activity against VRE (51), lack of activity against E. faecalis (6), and musculoskeletal toxicities in approximately 50% of the population, and because it requires the use of a central line for administration (52). Daptomycin is commonly used for the treatment of VRE infections (53), although the optimal dose and combinations are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Linezolid has inherent bacteriostatic activity (6,44) and can cause myelosuppression (45,46), and failure in bacteremia and IE has been documented in animal studies and human case reports (47)(48)(49)(50). The use of quinupristin-dalfopristin is also limited, because it demonstrates inherent bacteriostatic activity against VRE (51), lack of activity against E. faecalis (6), and musculoskeletal toxicities in approximately 50% of the population, and because it requires the use of a central line for administration (52). Daptomycin is commonly used for the treatment of VRE infections (53), although the optimal dose and combinations are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…13 (31%) were attributed to Ciprofloxacin (Linden et al, 2001). This is at variance with a study where no cases of Achilles tendon rupture were found in 2, 122 Ciprofloxacin treated patients (Shinohara et al, 1997).…”
Section: Human Studiesmentioning
confidence: 78%
“…Quinupristin/Dalfopristin ist ein Hemmstoff von Cytochrom-P450-3A4,sodass potenzielle Medikamenteninteraktionen beachtet werden müssen.Zu den häufigsten Nebenwirkungen gehören Arthralgien und Myalgien.Nebenwirkungen,wie Übelkeit,Erbrechen,Diarrhö und Hautausschlag wurden nicht mehr als bei anderen Antibiotika beobachtet. Leberenzym-und Bilirubinerhöhungen im Serum sind selten und gehören zu den am meisten beobachteten laborchemischen Veränderungen [9,11].…”
Section: Streptogramineunclassified